Analisis Pengembangan Strategi Bersaing Limasan Cafe Karawang - Nurjanah; Puji isyanto; Neni Sumarni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Limasan Karawang Coffee Shop, as one of the micro, small and medium enterprise (MSME) units in Karawang, has become a popular destination for young people and teenagers to enjoy the cafe atmosphere and the various coffee products on offer. This research aims to identify and analyze the competitive strategies that have been implemented by the Limasan Karawang Coffee Shop. This research uses qualitative descriptive analysis. Business Model Canvas (BMC) analysis is used to do this. Primary and secondary data were used in this research. Primary data was obtained from observations and in-depth interviews related to creating competitive strategies for the Limasan Karawang Coffee Shop which was the subject of the research. The results of research conducted by researchers in a study entitled "Analysis of the Competitive Strategy Development of Limasan Cafe" using the Business Model Canvas Approach confirm that the Business Model Canvas is an effective method as a foundation for generating strategic alternatives and establishing new strategies for the company. To help define, analyze, Designing a business model, the Business Model Canvas (BMC), consists of nine elements that represent all aspects of the business. This concept can serve as an effective tool for describing business models and developing new strategies